Nitrogen Fertilizer Rate and Cultivar Interaction Effects on Nitrogen Recovery, Utilization Efficiency, and Agronomic Performance of Spring Barley. (10th May 2012) - Anbessa, Yadeta; Juskiw, Patricia
Abstract : A study was carried out at Lacombe, Alberta, to develop baseline information on nitrogen recovery, utilization efficiency, and agronomic performance of spring barley. This information may enable us to understand where the inefficiencies of N nutrition may lay and determine strategies to improve nitrogen use efficiency (NUE). Three divergent cultivars, "Manley" (two-rowed, tall, late maturing), "Noble" (six-rowed, mid-height, intermediate maturing), and "Tukwa" (six-rowed, semidwarf, early maturing), were grown under low (0 kg ha -1 ), moderate (50 kg ha -1 ) and high (100 kg ha -1 ) rates of applied N fertilization. Both N recovery and utilization efficiency decreased with the increase in rate of applied N fertilizer, and NUE declined from 45 kg kg -1 N under the low N treatment to 33 kg kg -1 N under the moderate treatment and 24 kg kg -1 N under the high N treatment. The test cultivars were comparable in N uptake, but Tukwa and Noble were more efficient in their utilization of the N taken up than Manley, particularly under high N. Subsequently, while grain yield of Tukwa and Noble had increased linearly with rate of N fertilizer, the grain yield of Manley showed a declining trend under high N. This implies that, where a high input condition is targeted, improvement in N utilization efficiency may need to be given due consideration.